DiI‐mediated analysis of presynaptic and postsynaptic structures in human postmortem brain tissue. Issue 18 (12th June 2019) - Das, Sujan C.; Chen, Danli; Callor, William Brandon; Christensen, Eric; Coon, Hilary; Williams, Megan E.
Abstract: Most cognitive and psychiatric disorders are thought to be disorders of the synapse, yet the precise synapse defects remain unknown. Because synapses are highly specialized anatomical structures, defects in synapse formation and function can often be observed as changes in microscale neuroanatomy. Unfortunately, few methods are available for accurate analysis of synaptic structures in human postmortem tissues. Here, we present a methodological pipeline for assessing presynaptic and postsynaptic structures in human postmortem tissue that is accurate, rapid, and relatively inexpensive. Our method uses small tissue blocks from postmortem human brains, immersion fixation, lipophilic dye (DiI) labeling, and confocal microscopy. As proof of principle, we analyzed presynaptic and postsynaptic structures from hippocampi of 13 individuals aged 4 months to 71 years. Our results indicate that postsynaptic CA1 dendritic spine shape and density do not change in adults, while presynaptic DG mossy fiber boutons undergo significant structural rearrangements with normal aging. This suggests that mossy fiber synapses, which play a major role in learning and memory, may remain dynamic throughout life. Importantly, we find that human CA1 spine densities observed using this method on tissue that is up to 28 h postmortem is comparable to prior studies using tissue with much shorter postmortem intervals. Thus, the ease of our protocol and suitability on tissue with longer postmortem intervals should facilitate higher‐powered studies of human presynaptic and postsynaptic structures in healthy and diseased states. Abstract : Because changes in synapse formation and function can often be observed by altered synapse structure, we sought to develop an inexpensive, easy, and accurate method for analyzing presynaptic and postsynaptic structures in human postmortem tissue. Small pieces of human postmortem brain tissue were immersion fixed and hippocampal neurons labeled with the common lipophilic dye, DiI. Analysis of human tissue from healthy controls aged across the lifespan revealed that while human postsynaptic CA1 spine density and morphology remains stable, human presynaptic DG mossy fiber synapses undergo significant structural remodeling with normal aging. The ease of our method and suitability on tissue with long postmortem intervals should facilitate higher powered studies of human presynaptic and postsynaptic structures in healthy and diseased states.